Multi-objective optimization of rural water supply system - W.T.P. Silva; L.T.Q. Vieira; D.M.S. Rosa; M.M. Campos; A.A. Santos; M.A.A. Souza (Ingeniería del Agua)
Lack of water in water supply systems forces people to take risk behaviors to health, which is very common in rural water supply systems (WSS-rural). The objective of this research was to develop and apply a multi-objective optimization model for WSS-rural in the county of Cuiabá, Mato Grosso State, Brazil. The research methodology consisted of: (1) formulation of the optimization model (OM); (2) application of OM; (3) analysis of results; and (4) computer implementation of OM. To solve the problem, it was proposed and used a load loss generator part. It was found that the problem of water shortage can be solved by small operational and structural modifications. It was developed a multi-objective OM for WSS-rural based on Multi-objective Nonlinear Integer Programming technique (MONLIP) implemented in OpenOffice.org environment. The developed OM was applied to a real case with satisfactory results.